Proinflammatory and Anti-Inflammatory Cytokines Mediated by NF-κB Factor as Prognostic Markers in Mammary Tumors - Gustavo Rodrigues Martins; Gabriela Bottaro Gelaleti; Marina Gobbe Moschetta; Larissa Bazela Maschio-Signorini; Debora Ap. Pires de Campos Zuccari (Hindawi Limited, 2016)
Inflammation results in the production of cytokines, such as interleukin- (IL-) 4 and IL-10 with immunosuppressive properties or IL-6 and TNF-α with procarcinogenic activity. Furthermore, NF-κB is the major link between inflammation and tumorigenesis. This study verified the interaction between active inflammatory cytokines in the tumor microenvironment and serum of female dogs with mammary tumors and their correlation with the clinicopathological characteristics and overall survival. Measurement of gene expression was performed by qPCR and protein levels by ELISA/Luminex. High gene and protein expression levels of NF-κB, IL-6, and TNF-α were found in association with characteristics that reflect worse prognosis and a negative correlation between TNF-α protein expression and survival time was observed (p<0.05). In contrast, high gene and protein expression levels of IL-4 and IL-10 were associated with characteristics of better prognosis and an increased level of IL-4 and a longer survival time of animals were obtained (p<0.05). In addition, there was a positive correlation between TNF-α and IL-6 expression in association with NF-κB. The results show a significant correlation of these cytokines with tumor development, associated with NF-κB expression and cytokines promodulation, showing that these biological factors could be used as predictive and prognostic markers in breast cancer.